Distingsi Teologis antara Hukum Musa dan Sepuluh Hukum Tuhan: Sebuah Kajian Reinterpretatif - Gulo, Rezeki Putra; Silaen, Riste Tioma; Zai, Erwin; Mbelanggedo, Nelci (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
This research employs a qualitative research method with a literature review approach. The reinterpretation of the differences between the Law of Moses and the Ten Commandments is an effort to contribute to the discourse on the growing misconceptions about the Law, which significantly deviate from biblical truth. The Old and New Testaments speak of two distinct laws: the Law of Moses and the Ten Commandments of God. Unfortunately, many Christians are unaware of this truth, leading to misconceptions about the definition of the Law that do not align with the Word of God. Based on the research findings, these two